Correlation between Body Mass Index and Lipid Profile in Second Trimester with Incidence of Hypertension in Third Trimester - Prasetyo, Ananto; Wantania, John J E; Suparman, Erna (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective : to determine the relationship of BMI (Body Mass Index) and lipid profile (total cholesterol, triglycerides, HDL, LDL, VLDV) in the second trimester of pregnancy with the incidence of hypertension in the third trimester of pregnancy Methods :this study is a prospective cohort. The research subjects were the second trimester pregnant women group which examined by BMI and lipid profile, then assessed the incidence of hypertension in third trimester. The study was conducted in Department of Obstetric and Gynecology and Prof.DR.RDKandou General Hospital, and affiliated hospital from January 2017 until May 2017. Data analyzed with SPSS version 2.0 Results:from 49 research subjects, based on age,most subject with age 20-34 years with 42 subjects (85.8%). Based on the parity obtained 27 subjects (55.2%) with multigravida. By education level, most are high school with 19 subjects (38,7%). From the occupation, most are housewives with 30 subjects (61.3%). Based on BMI, most were subjects with normal BMI with 21 subjects (42.9%). Pearson test showed a significant association between BMI with total cholesterol (r = 0,500 and p = 0,000), whereas Spearman test showed significant relation between BMI with LDL cholesterol (r = 0,416 and p = 0,003) and significant relation between second trimester LDL cholesterol with third trimester diastolic blood pressure(r = 0.303 and p = 0.034). Conclusions:there was a significant correlation between BMI with total cholesterol & LDL in second trimester  and there was significant correlation between LDL in second trimester and third trimesterdiastolic blood pressure. Keywords:BMI,total cholesterol, VLDL, TG, LDL, HDL, hypertension.   Abstrak Tujuan : Untuk mengetahui hubungan IMT (Index Massa Tubuh)danprofil lipid ( kolesterol total, trigliserida, HDL, LDL, VLDV)  pada trimester kedua kehamilan dengan kejadian hipertensi pada trimester ketigak ehamilan. Metode : Penelitian ini merupakan kohort prospektif. Subjek penelitian adalah kelompok ibu hamil trimester kedua yang diperiksa IMT dan profil lipidnya, kemudian dinilai kejadian hipertensi pada trimester ketiga. Penelitian dilakukan di Departemen Obstetri dan Ginekologi  Rumah Sakit Umum Pusat (RSUP) Prof.DR.R.D Kandou, dan RS jejaring mulai Januari 2017 sampai Mei 2017. Data dianalisa dengan SPSS versi 2.0 Hasil : Dari 49 subjek penelitian, berdasarkan usia paling banyak usia  20 – 34 tahun dengan 42  subjek (85,8%). Berdasarkan paritas didapatkan 27 subjek (55,2%) dengan multigravida. Berdasarkan pendidikan, paling banyak adalah SMA dengan 19 subjek (38,7%). Dari jenis pekerjaan, paling banyak adalah ibu rumah tangga dengan 30 subjek (61,3%). Berdasarkan IMT, paling banyak adalah subjek dengan IMT normal dengan 21 subjek (42,9%). Uji Pearson menunjukkan hubungan bermakna antara IMT dengan kolesterol total (r = 0,500 dan p = 0,000), sedangkan Uji Spearman menunjukkan hubungan bermakna antara IMT dengan kolesterol LDL (r = 0,416 dan p = 0,003) dan hubungan bermakna antara kolesterol LDL trimester kedua dengan tekanan darah diastol trimester ketiga  (r = 0,303 dan p = 0,034). Kesimpulan : Terdapat hubungan bermakna antara IMT dengan kolesterol total, LDL trimester kedua dan terdapat hubungan bermakna antara LDL trimester kedua dengan tekanan darah diastol trimester ketiga. Kata kunci :IMT, kolesterol total, VLDL, TG, LDL, HDL, hipertensi.